Skincare practices in extremely premature infants: A survey of tertiary neonatal intensive care units from Australia and New Zealand. (18th June 2021) - Mishra, Umesh; Jani, Pranav; Maheshwari, Rajesh; Shah, Dharmesh; D'Cruz, Daphne; Priyadarshi, Archana; Galea, Claire; Lowe, Krista; Marceau, James; Wright, Audrey
Abstract : Aim: To investigate skincare practices in the first 2 weeks of life in extremely premature infants across tertiary neonatal intensive care units (NICUs). Methods: A web‐based secure survey invite was emailed to the medical directors of tertiary NICUs. The survey included questions on various aspects of skincare practices in the first 2 weeks of life in extremely premature infants (born before 28 weeks gestation). The person most familiar with local skincare practices was asked to complete the survey and only one response per unit was requested. We performed a descriptive analysis. Results: We received responses from 30 out of 32 NICUs (response rate 93%). Twenty‐five NICUs (89%) reported offering resuscitation and intensive care to infants born at ≥23 weeks gestation. All NICUs reported occurrences of skin breakdown, including medical adhesive‐related skin injury (30%), abrasion/friction‐associated skin injury (46%), perineal skin breakdown (55%), pressure site injury (47%) and diaper dermatitis (60%). A high level of consensus (≥75%) was observed for certain practices, such as the use of polyethylene occlusive plastic wraps at birth and aqueous chlorhexidine solution for sterile procedures, but a low level of consensus (<25%) was observed for many other practices, including the skin risk assessment tool used. Conclusions: Skin injuries in extremely premature infants are common and skincare practices vary considerably amongst NICUs. Clinical practice improvement projects and further clinical research will help improve consistency amongst NICUs. Further research is needed to assist the development of evidence‐based guidelines and benchmarking for skincare practices in these vulnerable infants.